Construction Supply Chain Performance Evaluation using The Supply Chain Operations Reference (Scor 12.0) (Case Study: Semarang-Demak Toll Road Project Package 2) - Nugroho Wahyu Jati; Mochamad Agung Wibowo; Maulida Asri (TEKNIK, 2026)
Inefficiencies in construction projects, aside from being caused by poor planning and control, are also attributed to delays in material delivery, especially for critical materials. One of the main causes of these delivery delays is suboptimal supply chain management. Therefore, it is essential to evaluate supply chain performance to identify and address these issues. Supply chain performance evaluation can utilize the SCOR 12.0 model, which has been widely applied in the manufacturing industry. A case study was conducted on the Semarang–Demak Toll Road Project Package 2, focusing on two key materials: precast full slabs and ready-mix concrete. The evaluation of supply chain performance employed the SCOR 12.0 model, which covers dimensions of reliability, responsiveness, agility, costs, and assets, as well as best practices implemented within the project. The research used a qualitative methodology, collecting data through questionnaires designed to assess supply chain performance indicators based on the SCOR 12.0 model, adapted for the construction context, and conducting interviews with project stakeholders and suppliers. The findings from the questionnaires and interviews were used to validate key performance indicators (KPIs), which were then scored on a Likert scale with five levels (5 = excellent, 4 = good, 3 = average, 2 = poor, 1 = very poor). The results of the supply chain performance assessment showed a score of 3.53 (good) for precast full slabs and a score of 3.8 (good) for ready-mix concrete.